2018
DOI: 10.2298/tsci160818110v
|View full text |Cite
|
Sign up to set email alerts
|

Movement of water drops in a forest fuel layer in the course of its thermal decomposition

Abstract: In this paper, we conducted an experimental investigation on water droplets gravitating in a layer of typical forest fuel (as illustrated by pine needle litter) in the course of its thermal decomposition. We used a high-speed (200 fps) video recording system, Tema Automotive software with continuous tracking of a moving object as well as a set of low-inertia (no more than 0.1 second) thermocouples. Similar experiments were performed at moderate temperatures (below the onset temperature of forest fuel pyrolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The water droplet sizes were controled by the optical diagnostic system [7] using "Shadow Photography" (SP) method. The droplet velocities were measured by the same system using "Particle Tracking Velocimetry" (PTV) method [8].…”
Section: The Methods and The Experimental Setupmentioning
confidence: 99%
“…The water droplet sizes were controled by the optical diagnostic system [7] using "Shadow Photography" (SP) method. The droplet velocities were measured by the same system using "Particle Tracking Velocimetry" (PTV) method [8].…”
Section: The Methods and The Experimental Setupmentioning
confidence: 99%
“…As a consequence, it is important to carry out the processes of promotion of typical fire extinguishing liquids through the layers of typical forest combustible materials. The results of experiments with water are given in [13]. It is advisable to develop this work on the most typical fire-extinguishing compositions with specialized additives.…”
Section: Introductionmentioning
confidence: 99%
“…This approach contributes the development of a large range of practical applications (for example, flame cleaning of liquids [3] and polydisperse firefighting [4]). …”
Section: Introductionmentioning
confidence: 99%
“…The results of investigations [3,4] are shown that the introduction of carbon particles into water droplets intensifies several times the phase transformations of the latter in a hightemperature (more than 700 K). It is established [3] that the evaporation of a liquid droplet containing a commensurate opaque inclusion in high-temperature gases is realized according to one of two schemes: 1) evaporation only from the free (external) surface of the drop; 2) evaporation from a free surface and intensive vaporization at internal interfaces.…”
Section: Introductionmentioning
confidence: 99%